PEMANFAATAN SABUT KELAPA MENJADI COCOPEAT DAN COCOFIBER DALAM UPAYA PENINGKATAN EKONOMI MASYARAKAT DESA GRUJUGAN SUMENEP - Dzulkarnain, Iskandar; Arendra, Anis; Dwitya Pramudita, Yoga; Jamilah, Jamilah (LPPM Universitas Bina Bangsa, 2025)
The coconut tree is a plantation crop where almost all parts of it can be utilized by humans and processed into industrial products. The products derived from coconuts include cocofiber, cocopeat, and baby fiber, which are raw materials for other products with higher value and selling prices. The goal of this community service activity is to utilize the coconut husk waste in Grujuga Village into cocopeat products that have a high selling value, thereby improving the economy in Grujugan Village, Gapura District. Through interviews and direct observation, ideas for industry managers were generated, both in terms of improving the production process and developing creative ideas to enhance product value. Based on this, community empowerment activities in the village are crucial to encourage the development of the village to become self-sufficient, as well as increase community knowledge in diversifying coconut commodities through the utilization and processing of coconut husk waste into cocopeat and cocofiber, thus producing superior village products. This will strongly support the village's program as an effort to improve the welfare of the community, the development of the creative economy, environmental management, and the ability to innovate to improve the living standards of the community in accordance with the achievement of the Sustainable Development Goals (SDGs).